2020
DOI: 10.1177/0091552120982021
|View full text |Cite
|
Sign up to set email alerts
|

Community College Study Abroad: An Event History Analysis

Abstract: Objective: The purpose of this study is twofold. First, this study explores individual student characteristics, specifically those related to demographics, financial need, academic characteristics, and social and cultural capitals, related to study abroad participation among community college students. Second, this study identifies when over the course of their studies community college students are most likely to participate in study abroad. Method: Data consist of student records provided by a large communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The critical equity-focused lens used to frame this study invites a perspective of results in the context of systems of “power, privilege, oppression, and advantage” (George-Mwangi & Yao, 2020, p. 5) that operate within and through international education. While international education, and especially U.S. study abroad, has traditionally been an exclusive and elitist activity (Contreras, 2015; Gore, 2005; Hoffa, 2007), reserved primarily for women (e.g., Lucas, 2018), White students (e.g., Salisbury et al, 2011); students from highly educated and financially well-off families (e.g., Lingo, 2019; Simon & Ainsworth, 2012), and students with high levels of academic achievement (e.g., Paus & Robinson, 2008), prior work suggests that community colleges may be poised to disrupt this narrative through the provision of educational opportunity to historically and currently underserved student populations (e.g., Raby & Rhodes, 2018; Whatley, 2021; Whatley & Raby, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The critical equity-focused lens used to frame this study invites a perspective of results in the context of systems of “power, privilege, oppression, and advantage” (George-Mwangi & Yao, 2020, p. 5) that operate within and through international education. While international education, and especially U.S. study abroad, has traditionally been an exclusive and elitist activity (Contreras, 2015; Gore, 2005; Hoffa, 2007), reserved primarily for women (e.g., Lucas, 2018), White students (e.g., Salisbury et al, 2011); students from highly educated and financially well-off families (e.g., Lingo, 2019; Simon & Ainsworth, 2012), and students with high levels of academic achievement (e.g., Paus & Robinson, 2008), prior work suggests that community colleges may be poised to disrupt this narrative through the provision of educational opportunity to historically and currently underserved student populations (e.g., Raby & Rhodes, 2018; Whatley, 2021; Whatley & Raby, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to study abroad participation are well-documented in the literature, and include not only the high cost of many study abroad programs, but also delayed progress towards degree completion as a result of participating, whether real or perceived, work and family obligations that prohibit students from leaving home for an extended period of time, and even a lack of role model and peer examples who have participated in an international educational experience (e.g., DeJong et al, 2010;Simon & Ainsworth, 2012;Soria & Troisi, 2014). Previous research indicates that, while community college study abroad is not immune to broad demographic trends in participation observed in other sectors of postsecondary education, wherein white students (e.g., Salisbury et al, 2011;Institute of International Education, 2019), students from higher socioeconomic status backgrounds (e.g., Lingo, 2019), and female-identifying students (e.g., Hurst, 2019) are more likely to participate, these trends may be weaker in the community college sector (e.g., Whatley, 2021). These results are promising for an equity-focused agenda and speak to the potential for community colleges to serve a democratizing function in US international education.…”
Section: Previous Literature Equity and Barriers In Access To Virtual...mentioning
confidence: 99%
“…Specifically, these characteristics include the student's age at enrollment in the community college, sex, racial/ethnic identity, and whether a student received Pell funding at any point during their enrollment, which we take to be an indicator, albeit imperfect, of low-income status (Rosinger & Ford, 2019). In the analyses described in the following section, we also include an indicator of students' first declared degree program, as prior research has shown that degree program is an important predictor of participation in study abroad (Whatley, 2021).…”
Section: Administrative Datamentioning
confidence: 99%
“…Community colleges serve over 11 million US students and, given the openaccess nature of their programming, tend to serve student populations that are more diverse than their four-year college and university counterparts (American Association of Community Colleges, 2021; Bailey & Morest, 2006;González Canché, 2018). Although international education programming often sits at the periphery of these institutions and reports lower participation rates compared to similar programming at four-year colleges and universities (IIE, 2020;Raby & Valeau, 2016), current research suggests that community colleges provide an important conduit to international education experience for underrepresented and underserved student populations, including those from minoritized racial/ethnic backgrounds and lower-income households (Whatley, 2021;Whatley & Raby, 2020). These students rely on their institutions to provide resources, financial and otherwise, that allow them to access international education opportunities and subsequent benefits.…”
Section: Introductionmentioning
confidence: 99%